Antidiabetics in combination with hydroxychloroquine improve antioxidant and hepatoprotective activities in alloxan-induced diabetic rats - Zannah, Shaheda; Islam, Monirul; Ali, Yusuf; Asaduzzaman, Md; Sarwar, Md Shahid; Bari, Abdul Alim Al; Rashid, Mamunur (Bangladesh Pharmaceutical Journal, 2015)
Hyperglycemia exerts toxic effects on the pancreatic ?-cells. This study investigated the hypothesis that the antidiabetic drugs glibenclamide and metformin, in combination with hydroxychloroquine (HCQ) offer additional protection for the pancreas against oxidative stress and produce hepatoprotective effect in alloxan-induced diabetic rats. Diabetes was induced in male Long-Evans rats by a single dose of alloxan (120 mg/kg; i.p.). Different groups of diabetic animals were treated with glibenclamide (10 mg/70 kg, i.p.), metformin (850 mg/70 kg, i.p.), HCQ (300 mg/70 kg, i.p.) and combination of both glibenclamide and metformin with HCQ, separately for a period of 28 days. Diabetic rats had significantly elevated levels of serum glutamate oxaloacetate transaminase (SGOT) and serum glutamate pyruvate transaminase (SGPT), while catalase (CAT) and superoxide dismutase (SOD) activity were significantly reduced. Glibenclamide and metformin produced no significant effects on antioxidant enzymes but both showed significant (p<0.05) result in reducing SGOT and SGPT level in diabetic rats. In contrast, the combination of glibenclamide or metformin with HCQ showed better effect on up-regulation of CAT and SOD activity and down-regulation of SGOT and SGPT activity in comparison with the antidiabetic drug alone. These findings suggest that, HCQ potentiates the effect of glibenclamide and metformin to protect pancreas against oxidative stress and produce hepatoprotective effect in diabetic rats. Bangladesh Pharmaceutical Journal 18(1): 72-77, 2015